Centenario de la Independencia y el próximo Bicentenario: Diálogo entre los Próceres de la nación, la «Patria Nueva» y el proyecto de comunidad cívica en el Perú - Casalino Sen, Carlota (2006)
This article has in five sections. Section 1 analyses the social and political context for the celebration of the Hundredth anniversary of the Peruvian Independence during the Administration of Augusto B. Leguia. Section 2 describes how this celebration took place. Section 3 explains the meaning of the Panteón de los Próceres in the context of this celebration. Section 4 goes beyond that period to show how, during that celebration, a new tradition is born reflecting the fragmentation of our society. Section 5 links the dates of those celebrations with the current period and with our own preparation and reflections about the second century of Peruvian independence.